Communicating nature during lockdown – How conservation and outdoor organisations use social media to facilitate local nature experiences. Issue 5 (10th August 2022) - Arts, Irma; Duckett, Dominic; Fischer, Anke; van der Wal, René
Abstract: Social media impact not only our communication and social interactions but also our relationships to the natural environment. Social media can increase understanding of our environment by offering information and sharing calls to action, while at the same time, they might present a glamourised, standardised picture of nature and distract from actual outdoor interactions. The COVID‐19 pandemic presents a unique opportunity to study the spaces created for interactions between the online and offline natural world, especially in countries where movement and thus outdoor activities were restricted during lockdowns. To understand these interactions, we investigated the social media communication of nature conservation and outdoor organisations by analysing Twitter posts of four prominent NGOs in Scotland. We found that during the first COVID‐19‐induced UK lockdown in spring 2020, Scottish nature conservation and outdoor organisations made distinctive efforts in supporting followers to connect with nature in the face of restrictions. Organisations showed signs of moving towards community‐building through sharing experiences often related to nearby nature, while calls for environmental action, more prominent in the previous year, receded in relative importance. Emphasis was put on sensory engagement with, and finding solace in the rhythm of, nature. References to taking action to protect nature now became linked to a green recovery from the pandemic. We conclude that NGOs used social media not as a space separate from the outdoors, but as an augmented space where online and offline interactions were interwoven and a space in which during the COVID‐19 pandemic, new avenues for engagement were being explored. Read the free Plain Language Summary for this article on the Journal blog. Abstract : Read the free Plain Language Summary for this article on the Journal blog.